2011
DOI: 10.1038/cddis.2011.38
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro assessment of pathways involved in contrast media-induced renal cells apoptosis

Abstract: Contrast-induced nephropathy accounts for >10% of all causes of hospital-acquired renal failure, causes a prolonged in-hospital stay and represents a powerful predictor of poor early and late outcome. Mechanisms of contrast-induced nephropathy are not completely understood. In vitro data suggests that contrast media (CM) induces a direct toxic effect on renal tubular cells through the activation of the intrinsic apoptotic pathway. It is unclear whether this effect has a role in the clinical setting. In this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
114
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(125 citation statements)
references
References 30 publications
7
114
0
4
Order By: Relevance
“…16 Our previous studies showed amlodipine and telmisartan could protect the renal tissue from nephrotoxicity induced by diatrizoate in rat model. 17,18 Another study indicated that enhanced formation of ROS in kidney after administration of CM play an important role in the development of CIAKI, 19 suggesting a protective effect of ROS scavenging or reducing ROS formation in CIAKI. Among these antioxidants, acetylcysteine (NAC) is the most studied agent for treatment of CIAKI.…”
Section: Discussionmentioning
confidence: 99%
“…16 Our previous studies showed amlodipine and telmisartan could protect the renal tissue from nephrotoxicity induced by diatrizoate in rat model. 17,18 Another study indicated that enhanced formation of ROS in kidney after administration of CM play an important role in the development of CIAKI, 19 suggesting a protective effect of ROS scavenging or reducing ROS formation in CIAKI. Among these antioxidants, acetylcysteine (NAC) is the most studied agent for treatment of CIAKI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that CM induce an increase in ROS production. 3,34 This leads to eventual activation of the stress kinases JNK1/2 and p38. For this reason, clinical trials have been performed with the use of various antioxidant compounds with the aim of lowering the occurrence of CIAKI by scavenging ROS.…”
Section: Mechanisms Of Prevention Of Cm-induced Renal Cell Damage Bymentioning
confidence: 99%
“…2 We have observed previously both in vitro and in vivo that CM induce apoptotic cell death via 3 important signaling pathways: (1) the reactive oxygen species (ROS) pathway, (2) the Jun N-terminal kinase (JNK)/p38 pathway, and (3) the intrinsic apoptosis pathway, which are triggered by CM in this sequence. 3,4 The causal relationship between these 3 sequential pathways supports the investigation of novel therapeutic approaches to prevent CIAKI.…”
mentioning
confidence: 99%
“…Various studies have demonstrated that excessive ROS promotes necroptosis in various cell types, whereas inhibiting ROS production reduces necroptosis (13)(14)(15)(16). In addition, previous studies revealed that ROS production is augmented in AKI, and that ROS lead to renal tubular epithelium injury via inflammasome activation, mitochondrion damage and tubular epithelium apoptosis (22)(23)(24)(25). To the best of our knowledge, there are no studies that have investigated the effect of ROS on necroptosis in renal tubular epithelium.…”
Section: Discussionmentioning
confidence: 99%